Implementasi E-Government di Kota Tangerang (Studi Kasus Aplikasi Tangerang Live) - Hastuti, Puji; Suherman, Agus; Utami, Pri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This research is motivated by innovative developments influencing support organizations to recognize e-government. Implementation of e-government is one of the efforts to create a responsible, straightforward, empowered, and productive climate of government. In 2016, the Mayor of Tangerang sent the Tangerang LIVE service program. With the Tangerang LIVE application, it is believed that they want to realize one of the e-city requirements, namely that all forms of activities in the City of Tangerang will be educated through extensive communication, especially as an intelligent city feature. This research aims to determine the implementation of e-government in Tangerang City on the Tangerang live application, determine the supporting variables and Utilization Implementation requirements, and decide on efforts to streamline the application implementation. This study uses Indrajit's (2004) hypothesis regarding the results of the audit and investigation by the Harvard JFK School of Government, which determines the milestones that must be owned in developing e-government further. These sections are Support, Capacity, and Value. This study uses a qualitative and descriptive methodology. The study results show that the implementation of the Tangerang LIVE application in Tangerang City has been carried out despite the lack of commitment from the local area. Socialization in the field must be carried out massively, starting from outreach through virtual entertainment, going directly to cities, and holding festivals. The Tangerang City Government, especially Diskominfo, needs to review the program that is being worked on thoroughly.